Pendidikan Kerohanian Berdasarkan Yohanes 15:1-8: Studi Eksegesis bagi Penguatan Teologi Pendidikan Agama Kristen (Jurnal Ilmu Pendidikan Keagamaan Kristen : Arastamar, 2025)
This study aims to analyze the meaning of spiritual maturity based on John 15:1-8 and its implications for Christian Religious Education, particularly in shaping the faith character of students in theological colleges and churches. The phenomenon of spiritual immaturity within churches and theological education institutions impacts the quality of spirituality and ministry performance. This research employed a qualitative method with an exegetical approach to text of John 15:1-8, supported by a literature review from accredited theological journals published in the last ten years. The novelty of this study lies in constructing a spiritual formation model based on the concepts of abiding in Christ (menō), divine spiritual pruning (kathairō), and the fruit of faith (karpos) as indicators of spiritual maturity. The findings show that an existential, active relationship with Christ, accompanied by spiritual disciplines and character purification, is essential for effective faith development. These results are implemented through exegetical-based discipleship curricula, prayer communities, periodic spiritual evaluations, and faith-purification retreats in theological education and local churches. This study contributes practically to the development of relational spirituality-based Christian Religious Education in Indonesia.